Equity of health care financing in South Korea: 1990-2016 - Tae-Jin Lee; Inuk Hwang; Hea-Lim Kim (BMC, 2021)
Abstract Background The National Health Insurance in Korea has been in operation for more than 30 years since having achieved universal health coverage in 1989 and has gone through several policy reforms. Despite its achievements, the Korean health insurance has some shortfalls, one of which concerns the fairness of paying for health care. Method Using the population representative Household Income and Expenditure Survey data in Korea, this study examined the yearly changes in the vertical equity of paying for health care between 1990 and 2016 by the source of financing using the Kakwani index, considering health insurance and other related policy reforms in Korea during this period. Results The study results suggest that direct tax was the most progressive mode of health care financing in all years, whereas indirect tax was proportional. The out-of-pocket payments were weakly regressive in all years. The Kakwani index for health insurance contributions was regressive but now is proportional to the ability to pay, whereas the Kakwani index for private health insurance premiums turned from progressive to weakly regressive. The Kakwani index for overall health care financing showed a weak regressivity during the study period. Discussion The overall health care financing in Korea has transformed from a slight regressivity to proportional over time between 1990 and 2016. It is expected that these changes were closely related to the improved equity of health insurance contributions from 1998 to 2008, which was the result of a merger of the health insurance societies and an amendment in the health insurance contribution structure. These results suggest that standardizing insurance managing organizations and financing rules potentially has positive implications for the equity of healthcare financing in a country where the major method of health care financing is social health insurance.